STRUKTUR KOMUNIKASI VISUAL FEED INSTAGRAM BANK BUMN DI TAHUN 2020: STUDI KASUS PADA BANK BRI, BNI DAN BTN DI TAHUN 2020 - Adya Mulya Prajana; Aisyi Syafikarani; Mohamad Tohir (Serat Rupa: Journal of Design, 2022)
Nowadays, many companies are using Instagram to build brand and marketing as BRI, BNI and BTN did. These three largest state-owned enterprise banks (BUMN) use Instagram accounts as their medium of interaction with their audience. Each has its own visual communication structure based on the character of followers, positioning and corporate identity. The visual communication structure is the primary strategy in attracting attention so that there is a direct interaction between consumer and the message conveyed by the company. Therefore, it is necessary to carry out further analysis to determine the visual, further analysis will be carried out to determine the visual communication structure of the three state-owned enterprise bank Instagram accounts. How followers can receive systematic and measurable visual messages to respond.. Thi study uses data search through field studies to obtain primary data from the Instagram account of thethree banks, followed by analyzing the data obtained using matrix analysis and visual analysis. The data that has been obtained will be analyzed using matrix analysis and visual analysis. The results of this study 1) All posters aim to attract followers' responses to participate in interacting in the comments column. 2) Each poster has its own visual communication structure based on the content of the message to be conveyed, whether express or implied. 3) The importance of message hierarchy on digital posters so that information is easy to understand. 4) Companies convey messages about company products or programs by creating quiz content.